Information communication technologies education in elementary school: a systematic literature review - Zuhri, Rois Saifuddin; Wilujeng, Insih; Haryanto, Haryanto; Ibda, Hamidulloh (Intelektual Pustaka Media Utama, 2024)
Implementing ICT education in elementary schools in the industrial era 4.0 is urgent. Several studies have explored ICT education in elementary schools, but few studies with systematic literature reviews remain. This article presents a literature review for 2019-2023 regarding ICT education in elementary schools. The Systematic Review Literature method and PRISMA protocol use Publish or Perish 7, VOSviewer, and NVIVO 12 Plus. The search results for Scopus articles contained 812, which were then filtered according to the theme to 61 for the study. The 61 articles were analyzed according to topic via NVIVO 12 Plus, and the results were described according to the research questions. ICT education in elementary school is a form of technology in learning to send, process, create, share, display, store, and exchange information. The characteristics of ICT education in elementary schools are ICT for online learning, communication interaction, digital media, software, inclusive, real-time, TPACK-based, and making students independent. The implementation of ICT education in elementary schools is carried out in learning, digital-based projects, curriculum, tools, and learning materials for Mathematics and language in elementary schools, which are supported by teachers’ digital competence. Future researchers must study ICT education in elementary schools according to technological developments.